Aspirin disrupts the mTOR-Raptor complex and potentiates the anti-cancer activities of sorafenib via mTORC1 inhibition. (10th October 2017) - Sun, Danni; Liu, Hongchun; Dai, Xiaoyang; Zheng, Xingling; Yan, Juan; Wei, Rongrui; Fu, Xuhong; Huang, Min; Shen, Aijun; Huang, Xun; Ding, Jian; Geng, Meiyu
Abstract: Aspirin is associated with a reduced risk of cancer and delayed progression of malignant disease. Adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)-mTOR signaling is believed to partially contribute to these anticancer effects, although the mechanism is unclear. In this study, we revealed the mechanism underlying the effects of aspirin on AMPK-mTOR signaling, and described a mechanism-based rationale for the use of aspirin in cancer therapy. We found that aspirin inhibited mTORC1 signaling through AMPK-dependent and -independent manners. Aspirin inhibited the AMPK-TSC pathway, thus resulting in the suppression of mTORC1 activity. In parallel, it directly disrupted the mTOR-raptor interaction. Additionally, the combination of aspirin and sorafenib showed synergetic effects via inhibiting mTORC1 signaling and the PI3K/AKT, MAPK/ERK pathways. Aspirin and sorafenib showed synergetic anticancer efficacy in the SMMC-7721 model. Our study provides mechanistic insights and a mechanism-based rationale for the roles of aspirin in cancer treatment. Highlights: Aspirin inhibits mTORC1 signaling in an AMPK-independent manner. Aspirin disrupts the mTOR-raptor interaction. mTORC1 inhibition contributed to the synergistic effect of aspirin combining with sorafenib.